Incrementing voltage reference photograph - Hess Photographic (1950)
This image was likely used as a reference for the arrangement of Beckman/Helipot voltage regulator microcircuits on a circuit board.
Keywords: Microelectronics; Voltage regulators; Beckman Instruments, Inc.